2003
DOI: 10.1093/molehr/gag023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-type Ca2+-channel blockade, K+ATP-channel opening and nitric oxide on human uterine contractility in relation to gestational age and labour

Abstract: Relative uterine inactivity during pregnancy changes to vigorous rhythmic contractility during labour. We hypothesized that mechanisms involved in the regulation of uterine quiescence and contractility differ between term and preterm myometrium and in labour and non-labour states. Myometrial strips, prepared from biopsies taken at Caesarean section from labouring and non-labouring women preterm and at term, were mounted in organ chambers for isometric tension recording. Oxytocin (10(-9) mol/l) was added to mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 25 publications
3
30
0
1
Order By: Relevance
“…Nifedipine (5 nM) inhibited the amplitude of oxytocin-stimulated contractions with less effect on frequency [41] and at μM concentrations completely eliminated contractile activity [42]. The effect of nifedipine on human myometrial strips was more marked in term not-in-labor than in term-labor specimens [43]. A significant proportion of oxytocin and PGF2α-induced contractions and increases in [Ca 2+ ] i in late pregnant guinea pig myometrium was attributed to Ca 2+ entry inhibited by L-type Ca blockers [44], as was the response in pregnant rat myometrial cell [45].…”
Section: Proteins Responsible For Membrane Calcium Entry and Exit Patmentioning
confidence: 95%
“…Nifedipine (5 nM) inhibited the amplitude of oxytocin-stimulated contractions with less effect on frequency [41] and at μM concentrations completely eliminated contractile activity [42]. The effect of nifedipine on human myometrial strips was more marked in term not-in-labor than in term-labor specimens [43]. A significant proportion of oxytocin and PGF2α-induced contractions and increases in [Ca 2+ ] i in late pregnant guinea pig myometrium was attributed to Ca 2+ entry inhibited by L-type Ca blockers [44], as was the response in pregnant rat myometrial cell [45].…”
Section: Proteins Responsible For Membrane Calcium Entry and Exit Patmentioning
confidence: 95%
“…These findings may indicate that in humans, down-regulation of K ATP channels may contribute to increased uterine excitability and induction of labor contractions in term pregnancy. In human myometrium, the expression of K ATP depends on both the gestational stage and the presence of labor contractions [41]. Pinacidil, a K ATP opener, inhibits oxytocin-induced contractions in late pregnant non-laboring myometrium [41].…”
Section: Bkca Channelsmentioning
confidence: 99%
“…In human myometrium, the expression of K ATP depends on both the gestational stage and the presence of labor contractions [41]. Pinacidil, a K ATP opener, inhibits oxytocin-induced contractions in late pregnant non-laboring myometrium [41]. This effect was attenuated in laboring myometrium from term and preterm uteri.…”
Section: Bkca Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mandi et al (2005) showed the ability of pinacidil to inhibit spontaneous rhythmic contractions and to antagonize oxytocin-induced contraction in the pregnant goat myometrium collected at the mid-gestation. The study of Longo et al (2003) also demonstrated that the increase in the expression and function of ATP-sensitive potassium channels may play an important role in the uterine preparation for pre-term or term labour.…”
Section: Discussionmentioning
confidence: 98%